Work Sights : The Visual Culture of Industry in Nineteenth-Century America - Schulman, Vanessa Meikle (Book collections on Project MUSE., 2015)
6. Laziness and Civilization: Picturing Sites of Social Control -- Conclusion: Twentieth-Century Echoes -- Notes -- Index -- About the Author -- Back Cover